World Index for Sustainability and Health (WISH), a globally applicable index for healthy diets from sustainable food systems - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
Based on the protocol developed by A4NH researchers, WISH has now been evaluated using datasets from Ethiopia, Viet Nam, Brazil and the Netherlands against indicators of nutrient adequacy and environmental sustainability. The WISH was presented in several fora, and the protocol paper has been cited several times.